Initial gene vector dosing for studying symptomatology of amyotrophic lateral sclerosis in non‐human primates. Issue 2 (29th January 2015) - Jackson, Kasey L.; Dayton, Robert D.; Fisher‐Perkins, Jeanne M.; Didier, Peter J.; Baker, Kate C.; Weimer, Maria; Gutierrez, Amparo; Cain, Cooper D.; Mathis, J. Michael; Gitcho, Michael A.; Bunnell, Bruce A.; Klein, Ronald L.
Abstract Background Most amyotrophic lateral sclerosis (ALS) research has focused on mice, but there are distinct differences in the functional neuroanatomy of the corticospinal pathway in primates vs. rodents. A non‐human primate model may be more sensitive and more predictive for therapeutic efficacy. Methods Rhesus macaques received recombinant adeno‐associated virus (AAV9) encoding either the ALS‐related pathological protein TDP‐43 or a green fluorescent protein (GFP) control by intravenous administration. Motor function and electromyography were assessed over a nine‐month expression interval followed by post‐mortem analyses. Results Recombinant TDP‐43 or GFP was stably expressed long term. Although the TDP‐43 subjects did not manifest severe paralysis and atrophy, there were trends of a partial disease state in the TDP‐43 subjects relative to the control. Conclusions These data indicate that a higher gene vector dose will likely be necessary for more robust effects, yet augur that a relevant primate model is feasible.